Standing on the shoulders of giants: two centuries of struggle against meningococcal disease. Issue 8 (August 2019) - Domingo, Pere; Pomar, Virginia; Mauri, Albert; Barquet, Nicolau
Summary: Meningococcal disease was first clinically characterised by Gaspard Vieusseux in 1805, and its causative agent was identified by Anton Weichselbaum in 1887, who named it Diplococcus intracellularis menigitidis. From the beginning, the disease was dreaded because of its epidemic nature, predilection for previously healthy children and adolescents, and high mortality. In the last decade of the 19th century, the concept of serum therapy for toxin-related bacterial diseases was identified. This concept was applied to meningococcal disease therapy, in an independent way, by Wilhelm Kolle, August von Wasserman, and Georg Jochmann in Germany, and Simon Flexner in the USA, resulting in the first successful approach for the treatment of meningococcal disease. During the first three decades of the 20th century, serum therapy was the standard treatment for meningococcal disease. With the advent of sulphamides first and then antibiotics, serum therapy was abandoned. The great challenges that infectious diseases medicine is facing and the awaiting menaces in the future in terms of increasing antibiotic resistance, emergence of new pathogens, and re-emergence of old ones without effective therapy, make passive immunotherapy a promising tool. Acknowledging the achievements of our predecessors might teach us some lessons to bring light to our future.